Coalition Politics in Contemporary India: Development and Dimensions - Rajkumar Singh (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2019)
On 11 April 2019 to 19 May 2019, seven phases of a general election will be conducted in India to select the State's 17th Lok Sabha. Before the general election, the law prohibits passing judgments to avoid inducement to voters. This provision, however, dissents from the mandate during the 1977 general election that showed that cultural homogeneity is not a reward for political stability and integration. Democratic stability is enhanced through group cross-cutting and politically relevant affiliations. This involves 1. application of power, in the sense of joint use of resources to determine outcomes'; 2. a ‘mixed motive situation' means the existence of both conflict and cooperation; and 3. collective activity, which involves the interaction of more than two units. In the Indian context, it can be argued that coalition politics has come to settle at the Indian federal level and that it cannot be viewed as a sudden and unexpected development. On a deeper analysis, it is reflective of a societal metamorphosis where in day by day a larger number of hitherto latent groups of Indian society are getting mobilized and politicized day by day. In this new coalition phase, what is under challenge are the status-quo and the unequal and unjust division of rewards and benefits. In today's society, especially having multi-layered caste and religion background, it is entirely possible to have a fractured mandate in which government is formed on